All-natural-molecule, bioluminescent photodynamic therapy results in complete tumor regression and prevents metastasis. (May 2023) - Yan, Hao; Forward, Sarah; Kim, Kwon-Hyeon; Wu, Yue; Hui, Jie; Kashiparekh, Anokhi; Yun, Seok-Hyun
Abstract: Self-luminescent photodynamic therapy (PDT) has gained attention owing to its potential to enable effective phototherapy without the bottleneck of shallow light penetration into tissues. However, the biosafety concerns and low cytotoxic effect of self-luminescent reagents in vivo have been problems. Here, we demonstrate efficacious bioluminescence (BL)-PDT by using bioluminescence resonance energy transfer (BRET) conjugates of a clinically approved photosensitizer, Chlorin e6, and a luciferase, Renilla reniformis ; both derived from biocompatible, natural molecules. With over 80% biophoton utilization efficiency and membrane-fusion liposome-assisted intracellular delivery, these conjugates produce effective, targeted cancer cell killing. Specifically, in an orthotopic mouse model of 4T1 triple-negative breast cancer, BL-PDT showed strong therapeutic effects on large primary tumors and a neoadjuvant outcome in invasive tumors. Furthermore, BL-PDT resulted in complete tumor remission and prevention of metastasis for early-stage tumors. Our results demonstrate the promise of molecularly-activated, clinically viable, depth-unlimited phototherapy.